CONCEPTUALIZATION OF ACADEMIC IDENTITY IN INTERDISCIPLINARY THEORETICAL AND METHODOLOGICAL DISCOURSE - Shadiuk, Tamara; Sarnavska, Oksana; Koberska, Tetiana (Theory and practice of design, 2025)
Purpose. The aim of this study is to formulate and substantiate the conceptual foundations of academic identity within the context of an interdisciplinary theoretical and methodological discourse, by defining its essence, structure, and mechanisms of formation in the contemporary academic environment. Methodology. The methodological framework of the study combines an interdisciplinary approach with a set of qualitative and theoretical-analytical methods. The method of conceptualization was employed to identify the key features of academic identity and to define its functional components. A structural- functional approach enabled the analysis of the role of identity in shaping institutional integrity and supporting the development strategy of higher education institutions. In turn, discourse analysis allowed for the interpretation of the communicative potential of identity in interaction with the sociocultural context of the academic environment, as well as understanding its role in shaping and maintaining institutional branding. Results. The article analyzes the transformations of academic identity in the digital age. It examines the evolution of the concept from the personal-professional to the institutional level, with a focus on the increasing role of visual identity and graphic design in the representation processes of higher education institutions. The study identifies the key components of academic identity: personal (individual self-identification of faculty and students), professional (competencies, teaching, and research activities), cultural (corporate culture, values), and institutional (branding, mission, visual elements). It is demonstrated that academic identity is increasingly articulated through institutional identity, shaped by visual, linguistic, and multimodal representational means. Visual identity (logos, color schemes, design of communication materials) is found to be not only a means of expression but also a factor in supporting a stable academic brand that unites members of the academic community. Scientific novelty. The study offers a comprehensive understanding of academic identity as a multi-level structure, wherein the institutional dimension acquires decisive significance in the digital era. It reveals the relationship between identification processes and the development of visual representation tools. The article emphasizes the role of the visual turn as a methodological foundation for contemporary research on academic identity, through which the broader social practice influencing visual communication strategies of modern universities is explained. Practical relevance. The findings may be utilized by higher education administrators to develop effective strategies for branding, visual communication, and strengthening institutional identity. Specifically, the article provides a theoretical basis for forming visual identity as a key element of educational marketing, contributing to student and partner engagement as well as enhancing the institution’s reputation.